Пошаговое объяснение:
3 А)
9х + 2у = 3
х - 3у = 10
х = 10 + 3у
1)
9(10 + 3у) + 2у = 3
90 + 27у + 2у = 3
27у + 2y = 3 - 90
29y = -87
y = -87 : 29
у = -3
2)
х = 10 + 3*(-3)
х = 10 + (-9)
х = 10 - 9
х = 1
ответ: (1; -3)
3 Б)
5х - 7у = 9 | : 5
6х + 5у = -16
х - 1,4у = 1,8
х = 1,8 + 1,4у
6(1,8 + 1,4у) + 5у = -16
10,8 + 8,4у + 5у = -16
8,4у + 5у = -16 - 10,8
13,4у = -26,8
у = -26,8 : 13,4
у = -2
х = 1,8 + 1,4*(-2)
х = 1,8 + (-2,8)
х = 1,8 - 2,8
х = -1
ответ: (-1; -2)
4 А)
х - 2у = -2
3х + 5у = 5
х = -2 + 2у
3(-2 + 2у) + 5у = 5
-6 + 6y + 5у = 5
6у + 5y = 5 + 6
11у = 11
у = 11 : 11
у = 1
х = -2 + 2*1
х = -2 + 2
х = 0
ответ: (0; 1)
4 Б)
3х + 2у = 6 | : 2
3х + 4у = 24
1,5х + у = 3
у = 3 - 1,5х
3х + 4(3 - 1,5х) = 24
3х + 12 - 6х = 24
3х - 6х = 24 - 12
-3х = 12
х = 12 : (-3)
х = -4
у = 3 - 1,5*(-4)
у = 3 - (-6)
у = 3 + 6
у = 9
ответ : (-4; 9)
Пошаговое объяснение:
3 А)
9х + 2у = 3
х - 3у = 10
9х + 2у = 3
х = 10 + 3у
1)
9х + 2у = 3
9(10 + 3у) + 2у = 3
90 + 27у + 2у = 3
27у + 2y = 3 - 90
29y = -87
y = -87 : 29
у = -3
2)
х = 10 + 3у
х = 10 + 3*(-3)
х = 10 + (-9)
х = 10 - 9
х = 1
ответ: (1; -3)
3 Б)
5х - 7у = 9 | : 5
6х + 5у = -16
х - 1,4у = 1,8
6х + 5у = -16
х = 1,8 + 1,4у
6х + 5у = -16
1)
6х + 5у = -16
6(1,8 + 1,4у) + 5у = -16
10,8 + 8,4у + 5у = -16
8,4у + 5у = -16 - 10,8
13,4у = -26,8
у = -26,8 : 13,4
у = -2
2)
х = 1,8 + 1,4у
х = 1,8 + 1,4*(-2)
х = 1,8 + (-2,8)
х = 1,8 - 2,8
х = -1
ответ: (-1; -2)
4 А)
х - 2у = -2
3х + 5у = 5
х = -2 + 2у
3х + 5у = 5
1)
3х + 5у = 5
3(-2 + 2у) + 5у = 5
-6 + 6y + 5у = 5
6у + 5y = 5 + 6
11у = 11
у = 11 : 11
у = 1
2)
х = -2 + 2у
х = -2 + 2*1
х = -2 + 2
х = 0
ответ: (0; 1)
4 Б)
3х + 2у = 6 | : 2
3х + 4у = 24
1,5х + у = 3
3х + 4у = 24
у = 3 - 1,5х
3х + 4у = 24
1)
3х + 4у = 24
3х + 4(3 - 1,5х) = 24
3х + 12 - 6х = 24
3х - 6х = 24 - 12
-3х = 12
х = 12 : (-3)
х = -4
2)
у = 3 - 1,5х
у = 3 - 1,5*(-4)
у = 3 - (-6)
у = 3 + 6
у = 9
ответ : (-4; 9)